Aspects of crop and socioeconomic management of the lima bean within northeastern Brazil - Ferreira Gomes, Regina Lucia; Soares, Cristiane Araújo [UNESP]; Gândara, Francisco Carlos; Lobo Burle, MarÍlia (My University, 2015)
Socioeconomic studies comprise an effective tool that captures the variables related to the production process. From this perspective, it is essential to understand the socioeconomic and environmental diagnoses of lima bean production in northeastern Brazil, considering that this legume is consumed in many different forms and is very important for human and animal feeding. Regarding the lima bean production system, the technology used is simple and rudimentary; there is no type of soil conservation management, and agricultural chemicals are not used for pest and disease control in crops, which is instead controlled naturally. Although farmers use this legume for consumption, a significant portion of them also sell the crop mainly within the municipality where they are grown. Regarding the aspects of the income composition of the farmers, most receive public policy contributions, and 90% do not reside within the production unit because most are not the landowners. There is a higher proportion of men working with lima bean crops, and most of them are married and live in brick houses, in which often there is no basic sanitation. Thus, creating development strategies more adequate for the lima bean farming conditions of northeastern Brazil would contribute to the improvement of the quality of life of the rural communities.
Keywords: Grain production; Infrastructure; Phaseolus lunatus; Phytotechnical practices